ANALYSIS OF REVENUE OF MF DESSERT MICRO SMALL AND MEDIUM ENTERPRISES IN PALU CITY - Mifta Khairani Nasution; Meity Ferdiana Paskual, Rita Yunus, Santi Yunus, Musdayati (Adisam Publisher, 2024)
MF Dessert is a company that produces haunted chocolate cake, mille crepes, and fruit salad made from wheat flour, sugar, eggs, butter, and fruit. This research aims to analyze the income of MSME Dessert businesses in Palu City. The research was carried out from August to December 2023 on Jl Ramba, Baiya sub-district, Tawaeli District, Palu City. The data analysis method uses an income analysis formula consisting of TC, TR, and Y (income). To calculate business viability, use the sales to cost ratio (R/C ratio) formula. The research results show that the average income from the Mf dessert business is IDR 3,752,000 per month and production costs are IDR 2,153,980 per month. These production costs consist of fixed costs of IDR 89,980 per month and variable costs of IDR 2,064,000 per month. Based on the results of data analysis, income from the Mf Dessert business in the city of Palu was IDR 1,598,020/month. Based on the calculation of business feasibility (R/C Ratio), a value (R/C Ratio) of 1.74 or 1.74 > 1 is obtained, which means that every cost incurred of IDR 1 produces a revenue of 1.74 so the revenue is greater than the capital invested. issued. So it can be concluded that the Mf Dessert business in this research is considered profitable and feasible.